Constructivist Character of the Technique of Role-Playing Games and its Autonomizing Values in the Glottodidactic Process - Surdyk, Augustyn (Wydawnictwo Uniwersytetu Mikołaja Kopernika, 2006)
To Augustyn Surdyk numerous assumptions of constructivism and constructionism in the educational context seem to correspond with the idea of autonomisation in foreign language didactics. He presents a comparison of selected aspects of the three theories in question on the example of an innovative communicative technique of Role-Playing Games applied in the process of teaching foreign languages at an advanced level. The conventions of the technique with its simplified rules have been borrowed from popular parlour games and adapted by the author to the conditions of language didactics. The elements of play and simulation incorporated in the technique allow it to be rated among techniques of ludic strategy. (from Preface to the book)
Keywords: constructivism; constructionism; autonomy in foreign language learning/teaching; technique of role-playing games